Pengembangan Aplikasi Autoplay dengan Konsep Context-Aware menggunakan Spotify API berbasis Android - Rofy Firmansyah Rachmandany; Agi Putra Kharisma; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Smartphone are the one of device that well-needed by people. Smartphone can be used for many things and have supporting sensors. It makes smartphone become highly potential device. That potential is utilized by an application called Spotify. Spotify is an aplication for streaming music, podcasts, and videos. To maximize the use of Spotify, an autoplay application developed in this study. This application has a context-aware concept that uses activity recognition to trigger Spotify. This design of this application uses the Object-Oriented (OO) method. This application is implemented by Java programming language and created by Android Studio IDE. This application testing uses Validation, Compatibility, and Usability method. In Validation Testing, all functions on this application can run normally. In Compatibility Testing performed on five devices with different Android version, all functions on this application can run normally. In Usability Testing, this application uses questionnaire with SUS (System Usability Scale) method. Based on the results from conducted research, the results of Usability Testing involved 10 (ten) respondents were 74.5%. Under the SUS method, the value is included as â€œGoodâ€ category and can be accepted by the users.